Trophic and proliferative effects of Shh on motor neurons in embryonic spinal cord culture from wildtype and G93A SOD1 mice - Ma, Xiaoxing (BioMed Central, 2013)
BACKGROUND: The developmental morphogen sonic hedgehog (Shh) may continue to play a trophic role in the support of terminally-differentiated motor neurons, of potential relevance to motor neuron disease. In addition, it may support the proliferation and differentiation of endogenous stem cells along motor neuronal lineages. As such, we have examined the trophic and proliferative effects of Shh supplementation or Shh antagonism in embryonic spinal cord cell cultures derived from wildtype or G93A SOD1 mice, a mouse model of amyotrophic lateral sclerosis. RESULTS: Shh supported survival, and stimulated growth of motor neurons, neurite outgrowth, and neurosphere formation in primary culture derived from both G93A SOD1 and WT mice. Shh increased the percentage of ciliated motor neurons, especially in G93A SOD1 culture. Shh-treated cultures showed increased neuronal proliferation compared to controls and especially cyclopamine treated cultures, from G93A SOD1 and WT mice. Moreover, Shh enhanced cell survival and differentiation of motor neuron precursors in WT culture. CONCLUSIONS: Shh is neurotrophic to motor neurons and has mitogenic effects in WT and mSOD1 G93A culture in vitro.